Clinical and laboratory passive fit assessment of implant‐supported zirconia restorations fabricated using conventional and digital workflow. (5th February 2020) - Rutkunas, Vygandas; Larsson, Christel; Vult von Steyern, Per; Mangano, Francesco; Gedrimiene, Agne
Abstract: Background: Long‐term success of implant‐supported restorations can be affected by the accuracy of the prosthodontic workflow which may differ between conventional and digital techniques. Purpose: The purpose was to compare the fit of two‐implant‐supported restorations, fabricated using conventional and digital workflows and to assess the influence of distance and angulation between the implants on the passive fit of the prosthesis. The SR test was selected to evaluate the fit of two‐implant‐supported zirconia restorations. Materials and Methods: Forty‐eight zirconia two‐implant‐supported restorations were fabricated according to conventional (group C, n = 24) and digital (group D, n = 24) workflows. The SR parameter was calculated as a difference of rotation angles of each screw in passive and nonpassive situations. SR values between groups C and D were compared by performing measurements intraorally, on master and control casts. Results: SR intraorally in group C (16.25 ± 15.52°) was higher than it was in group D (13.85 ± 10.78°), but the difference was not statistically significant ( P = .557). While measuring SR on the master cast, group C SR (6.04 ± 7.43°) had lower values than group D (13.12 ± 13.86°) ( P = .0039). No statistically significant correlations were found between SR measurements and inter‐implant distance or angulation. Restorations with inter‐implant angle higher than 10° differed significantly from those with less than 10° angulation. Conclusions: Digital restorations had a better fit on the control cast, which was used as a reference in this study. Angulation of more than 10° between the implants could negatively affect the passive fit of the digitally fabricated restorations intraorally.